(3aUd eNJUQ aj eYQaI JQcjH GdQhM hGdfaS hGdLSOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3aUd eNJUQ ai eYQaI JQcjH GdQhM hGdfaS hGdLSO CeG JUYjO GdQhM s
(3BNQgG (B:s
(3SMbgeG ai UaQI GdHjVQ hGQei hGMO efg Ydi NeSI ef GdRgQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B(3/2526) s
Keywords: (3GdadSaI hGdefWbs